MOTIVASI BERAGAMA DALAM AGAMA ISLAM - Fadliyanur (AL-FALAH: Jurnal Keislaman dan Kemasyarakatan, 2026)
Human spiritual life depends on religious motivation, which directs them to behave in accordance with divine teachings. The purpose of this study is to examine the true nature of religious motivation, the Islamic psychological perspective on motivation, and the classification of religious motivations found in Muslims. The method used was a study of religious literature, including literature on the psychology of religion, as well as the text of the Quran. The results indicate that the Islamic religious motivation stems from human nature to seek protection and tranquility in Allah SWT. This motivation is divided into intrinsic and extrinsic aspects, and is influenced by elements of the physical, spiritual, and spiritual dimensions. Therefore, strong religious motivation serves as a primary driver for maintaining consistent worship and building positive character amidst the challenges of the times.